The Effect of Entrepreneurial Education Program on Entrepreneurial Self-Efficacy in Some Selected South Africa’s Universities: Students’ Perception - EM. Rankhumise; ME. Letsoalo (CV. Literasi Indonesia, 2023)
Entrepreneurship can greatly contribute to economic growth and graduate employment. Many university graduates may find that becoming an entrepreneur is the solution to their recruitment issues. This exploratory cross-sectional quantitative study at the Tshwane University of Technology and Walter Sisulu University aims to learn about entrepreneurship education students' perceptions of the impact of the curriculum on their capacity to interact with the business sector. A total of 484 students (279 TUT and 205 WSU) volunteered to participate. The results indicated that students at both universities valued the universities' intervention through the entrepreneurial education program. It was also discovered that entrepreneurship education continues to play a significant part in the lives of all motivated business students. The delivery of entrepreneurship education should be enhanced to ensure that the students benefit and have the propensity to start their businesses. In so doing, less unemployment of graduates would be experienced. Further studies should be conducted in a broader scope by embarking on other universities beyond the current ones surveyed to enable the findings to be generalized.